The tax elasticity of formal work in African countries - Andrew D. McKay; Jukka Pirttilä; Caroline Schimanski (The United Nations University World Institute for Development Economics Research (UNU-WIDER), 2019)
A key policy problem in most developing countries is the size of the informal sector and its persistence over time. In need to increase their tax revenues, policy makers face a trade-off between decreasing tax rates (making formalizing potentially more attractive) and alternatively raising tax rates (potentially slowing down the formalization of the economy if people prefer informal employment or self-employment). Evidence on formal versus informal wages and job characteristics in different sectors and the impact of tax changes on the extent of informality in developing countries is, however, very limited. This paper estimates the tax responsiveness of the extensive margin of formality, that is the propensity to be a formal rather than informal worker, for four sub-Saharan African countries. Using repeated cross-sections of household data and applying grouping estimator techniques, this paper does not find robust effects of taxes on the extent of formal work, although in a pooled sample taxes appear to lower the share of formal workers in some specifications.
Keywords: H31; J20; O17; 330; developing countries; informality; labour supply; sub-Saharan Africa; taxation